Swap curve steepener - Varma, J. R. (SAGE Knowledge. Cases., 2017)
The case is about a decision problem facing James on whether or not to invest in a structured product called the "CMS Steepener" issued by a large US investment bank. The payoff from the product is linked to two constant maturity swap (CMS) rates, and the investor profits if the difference between the two CMS rates increases or, alternatively, if the CMS curve steepens. The case describes the risks that investing in such a product poses, and presents relevant data on the CMS rates, term structure and recent financial history of the issuer to help resolve James's decision problem.